Acute effect of a dynamic-based stretching warm-up on primary school students’ explosive strength - Merino-Marban, Rafael; Fernández-Agulló, Rubén; Mayorga-Vega, Daniel (My University, 2022)
The impact of different types of warm-up protocol on children’s performance is clearly an unresolved issue that has not yet been satisfactorily investigated. PURPOSE: The aim of the present study was to compare the acute effect of a dynamicbased stretching warm-up on standing long jump performance in primary schoolchildren. METHODS: From the total of 186 students (53.5% females) who were invited to participate in the present study. Finally, 143 (53.1% females) students satisfactorily met the exclusion criteria (aged 8-11 years old). A cluster-randomized crossover trial in the Physical Education setting was carried on. The clusters were pre-established classes in the school setting. The crossover design was chosen to eliminate any negligible carry over effect. RESULTS: The results of the Multilevel Lineal Model showed that after the dynamic-based stretching warm-up students had statistically significantly higher standing long jump scores than after the no stretching warm-up (no stretching, adjusted M = 126.81 cm; SE = 1.54; dynamic stretching, adjusted M = 137.99 cm; SE = 1.54; - 2LL = 2314.892, F = 131.155, p < 0.001, d = 0.50). CONCLUSION: The dynamic-bouncing stretch as a final part of a warm-up improves explosive strength performance in primary schoolchildren. And seems to be a good option before carrying out explosive strength activities of the lower body.
Keywords: Ejercicio físico; Educación física para niños; Bouncing stretching; Warm up; Physical Education